f(n)=2*f(n-1)

Simple and best practice solution for f(n)=2*f(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(n)=2*f(n-1) equation:


Simplifying
f(n) = 2f(n + -1)

Multiply f * n
fn = 2f(n + -1)

Reorder the terms:
fn = 2f(-1 + n)
fn = (-1 * 2f + n * 2f)
fn = (-2f + 2fn)

Solving
fn = -2f + 2fn

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '2f' to each side of the equation.
2f + fn = -2f + 2f + 2fn

Combine like terms: -2f + 2f = 0
2f + fn = 0 + 2fn
2f + fn = 2fn

Add '-2fn' to each side of the equation.
2f + fn + -2fn = 2fn + -2fn

Combine like terms: fn + -2fn = -1fn
2f + -1fn = 2fn + -2fn

Combine like terms: 2fn + -2fn = 0
2f + -1fn = 0

Factor out the Greatest Common Factor (GCF), 'f'.
f(2 + -1n) = 0

Subproblem 1

Set the factor 'f' equal to zero and attempt to solve: Simplifying f = 0 Solving f = 0 Move all terms containing f to the left, all other terms to the right. Simplifying f = 0

Subproblem 2

Set the factor '(2 + -1n)' equal to zero and attempt to solve: Simplifying 2 + -1n = 0 Solving 2 + -1n = 0 Move all terms containing f to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1n = 0 + -2 -1n = 0 + -2 Combine like terms: 0 + -2 = -2 -1n = -2 Add 'n' to each side of the equation. -1n + n = -2 + n Combine like terms: -1n + n = 0 0 = -2 + n Simplifying 0 = -2 + n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

f = {0}

See similar equations:

| 3(3z+1)-8=40 | | -1440=-15(-15x-29) | | 8u-1=8 | | (6+k)+12=23 | | 3(2x-7)-4(x-1)= | | 2h+10=66 | | 2h+10=66 | | y-8+124=180 | | -41=5x+9 | | -1440=-15(-15x-21) | | 1.4a+10=17 | | 6x+13=5x | | n+36=5m | | (X-3)(x+4)=x^2-5x+20 | | 9+2z-8=7z+7-4z | | a(-12)=b | | 0.6x-0.33=1 | | 4000=5.5x-460.5 | | x+16=2x-16 | | v=3.141592654(36)(16) | | 8(t-3)+4=4(3t+5)-9 | | 3x^2+7x-11=17-10x | | v=3.141592654(36)2(16) | | y-63x-3=0 | | 5.8a+14=66.2 | | 0.6-5x=2 | | 6x+1=x+37 | | 3*3.33-12= | | Q=M+Mrt | | 3x^2-432=-288 | | 3(2x-1)-7=-16 | | 10.50+25x=340 |

Equations solver categories